Enhanced osteogenic activities of polyetheretherketone surface modified by poly(sodium p‐styrene sulfonate) via ultraviolet‐induced polymerization. Issue 38 (7th March 2020) - Ma, Zhangyu; Li, Linlong; Shi, Xincui; Wang, Zongliang; Guo, Min; Wang, Yu; Jiao, Zixue; Zhang, Congxiao; Zhang, Peibiao
Abstract: Polyetheretherketone (PEEK) is a promising bone and dental tissue engineering material with excellent mechanical properties and biocompatibility, but its biological inertness deficiency limits its clinical applications. In this study, poly(sodium p‐styrene sulfonate) (pNaSS) was grafted onto PEEK surface by ultraviolet (UV) induced polymerization to enhance its osteogenic activities. Attenuated total reflectance Fourier transformed Infrared (ATR‐FTIR) spectroscopy, scanning electron microscopy (SEM), and contact angle (CA) analysis were carried out to prove the success of grafting polymerization. Toluidine blue O (TBO) colorimetric assay was utilized to quantify the graft amounts of pNaSS. Results showed that the amounts of grafted pNaSS on the PEEK surface could be well‐controlled from 0.59 ± 0.07 mmol/cm 2 to 5.08 ± 0.20 mmol/cm 2, through adjusting the UV irradiation time and monomer concentration. The hydrophilicity of PEEK surface was increased and the in vitro mineralization ability was promoted with the introduction of pNaSS. Besides, this surface modification method did not influence the intrinsic mechanical properties of PEEK. in vitro biological studies revealed that cell adhesion, proliferation, and osteogenic differentiation of MC3T3‐E1 cells were enhanced with the increase of graft amounts. Abstract : After modified by pNaSS, the PEEK surface exhibited the abilities of promoting the proliferation, cell osteogenic differentiation MC3T3‐E1 cells.